Uma proposta para a unificaç\~ao dos benefícios sociais de crianças, jovens e adultos pobres e vulneráveis - Sergei Soares; Letícia Bartholo; Rafael Guerreiro Osorio (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– Social protection policy in Brazil is a historically built patchwork of programs that pay different values to people in the same situation, leaves many unprotected (in particular, 17 million children), is fraught with duplications and other inefficiencies. This note proposes an approach within which can join all transfers to individuals vulnerable to poverty and children within a single framework. The budgets of the Bolsa Família, Abono Salarial, Salário-Família programs and the child income tax deduction together add up to R 52 billion (about USD 15 billion). With these resources, it is possible to propose a new transfer program based on a Universal Child Benefit and targeted Extreme Poverty Grant whose impacts on poverty and inequality are twice those of the four programs above.
Keywords: I38; 330; social protection; universal child grant; Bolsa Família; Abono Salarial; Salário-Família